MOTOR VEHICLE SAFETY SYSTEM BASED MIKROKONTROLLER ATmega328 USE SMS GATE WAY AND MODUL GPS - Zul Azhar; Fathurrahman Fathurrahman (FISITEK: Jurnal Ilmu Fisika dan Teknologi, 2020)
Motorcycle theft cases are increasing lately. However, the level of successful case disclosure by the police is classified as minimal. One of the reasons is the difficulty of the investigating team to locate the stolen vehicle. One solution that can be done is to install a tracker on a motorcycle. With the development of technology, we can use GPS devices as a tool to track vehicles from theft. The general objective of this research is to reduce the crime rate of motorcycle theft that currently occurs in Indonesia. The specific design objectives are: (1). Facilitate the security apparatus (2). Eliminate public anxiety about motorbike theft cases. For that we need a better security system as a safety for motor vehicles. This tool is equipped with features or services that support services on motorbikes, namely: SMS / SMS Gateway/ SIM800L Module, ATMega328 Microcontroller, GPS (Global Positioning System) Module, and other supporting devices. This tool is connected to an Android device with a GPS tracking system by showing the location of the missing motor vehicle. It is hoped that this security system design can increase the level of security and reduce cases of theft in motor vehicles. This system has also been tested on motorbikes with good results.